2021
DOI: 10.1177/11786388211014917
|View full text |Cite
|
Sign up to set email alerts
|

Carrot Juice Consumption Reduces High Fructose-Induced Adiposity in Rats and Body Weight and BMI in Type 2 Diabetic Subjects

Abstract: Nutritional intervention is a key strategy in the control and management of non-communicable diseases. Here, initially, we evaluated the effects of carrot juice (CJ) on some of the physical and biochemical parameters in rats fed with high-fructose diet, then in type 2 diabetic subjects. For the animal study, weanling male Wistar rats were given control (n = 6) or high fructose (HFr; n = 24) diet for 8 weeks. Then, the HFr group rats were subdivided into 4 groups (n = 6 in each) and continued either on HFr diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
(65 reference statements)
0
5
0
4
Order By: Relevance
“…The strengthened ability of the human gut microbiota to metabolize carbohydrate and lipid is likely due to the increased fermentation of dietary fibers and lipid-soluble vitamins from the carrot juice. Previous studies have indicated that drinking carrot juice could help to reduce the body weight and body mass index in type 2 diabetic subjects [5]. However, the detailed nutritional mechanism is largely unknown.…”
Section: Carrot Juice Changed the Metabolic Functions Of The Human Gu...mentioning
confidence: 99%
See 1 more Smart Citation
“…The strengthened ability of the human gut microbiota to metabolize carbohydrate and lipid is likely due to the increased fermentation of dietary fibers and lipid-soluble vitamins from the carrot juice. Previous studies have indicated that drinking carrot juice could help to reduce the body weight and body mass index in type 2 diabetic subjects [5]. However, the detailed nutritional mechanism is largely unknown.…”
Section: Carrot Juice Changed the Metabolic Functions Of The Human Gu...mentioning
confidence: 99%
“…Previous studies have indicated that drinking carrot juice could increase the total antioxidant status and decreases lipid peroxidation in adults [4]. Besides, carrot juice consumption was also found to reduce the body weight and body mass index in type 2 diabetic subjects [5]. However, although the biological and nutritional activities of carrot juice have been extensively studied, what effect it has on the human gut microbiota has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Beberapa hal yang dilakukan dalam ME, meliputi (Hu et al, 2020): -mempertimbangkan spektrum makanan yang lebih luas: dari mana makanan itu berasal, bagaimana makanan itu disiapkan, dan siapa yang menyiapkannya -memperhatikan isyarat internal dan eksternal yang memengaruhi seberapa banyak kita makan -memperhatikan penampilan, rasa, bau, dan rasa makanan Konsumsi jus buah dan sayur banyak memberikan manfaat pada individu dengan atau tanpa penyakit kronis seperti diabetes melitus (DM). Penelitian pada subjek DM yang diberikan konsumsi 50mL jus wortel segar (freshly prepared raw carrot) dengan kandungan 2400µg β-carotene per hari selama 6 minggu secara signifikan menurunkan berat badan (P=.014), memungkinkan menurunkan persentase lemak tubuh (P=.029) (Mahesh et al, 2021). Adapun penelitian di Saudi Arabia, menunjukkan pada Wanita, intake juice segar 1 sampai 4 porsi per minggu dan 5 porsi atau lebih berhubungan signifikan dengan kadar gula darah normal dibandingkan dengan yang tidak mengkonsumsi jus segar (Jambi et al, 2020).…”
Section: Kajian Pustakaunclassified
“…Kombinasi manis-asam seperti jus wortel-nanas adalah rasa jus yang paling disukai responden. Jus wortel yang dikonsumsi secara konsisten minimal 6 minggu bermanfaat untuk menurunkan body mass index dan mereduksi tumpukan lemak tubuh (Mahesh et al, 2021).…”
Section: Hasil Penelitian Dan Pembahasanunclassified
“…According to some studies fruit juice consumption reported a positive association with adiposity (9) while other failed to nd a positive association between fruit juice and anthropometric indices (10)(11)(12). Water consumption maybe an important strategy for prevention and treatment of obesity (13).…”
Section: Introductionmentioning
confidence: 99%